STATE OF THE ART IN THE TREATMENT OF EXTRADURAL SPINAL TUMORS - Alikhodjayeva, G.A.; Akhmediev, T.M. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Introduction. Timely diagnosis of tumors of the thoracic spine at an early stage of the disease creates conditions for the choice of adequate tactics of surgical treatment with the preservation of vital anatomical structures. The purpose of the study: to analyze the results of surgical treatment of extradural tumors of the thoracic spine, depending on the choice of surgical treatment tactics. Materials and methods. The material of the study are patients with extradural tumors of the thoracic spine aged 10 to 50 years who were treated at the Republican Specialized Scientific and Practical Medical Center of Neurosurgery in the period 2019-2021. The following methods were used in the investigation: clinical neurological, X-ray, MRI, MSCT studies, scintigraphic research. Methods of surgical intervention: Laminectomy with removal of an extradural tumor of the thoracic spine without stabilization of the vertebral-motor segment Laminectomy with removal of an extradural tumor of the thoracic spine with stabilization of the vertebral-motor segment All patients were divided into 2 groups: The main group, patients underwent removal of an extradural tumor of the thoracic spine with stabilization of the spine (stabilizing); Control group, patients underwent removal of an extradural tumor of the thoracic spine without spinal stabilization (decompressive). We used the following scales: determination of the general condition of patients according to the Karnovsky scale, the pain intensity scale (Dennis, 1989), the scale of motor and sensory functions according to Frankel (1992), assessment of sensitivity disorders. Results. In the surgical treatment of tumors of the thoracic spine, we applied 2 main types of interventions: stabilizing and decompressive operations. In decompression-stabilizing operations, posterior-median access is very convenient in terms of decompression and removal of the tumor. Conclusion. Indications for surgical treatment of extradural spinal cord tumors were the presence of intense pain syndrome, compression of the spinal cord, progressive neurological disorders, gross instability of the spinal-motor segment. The best results were noted in the group of patients who underwent spinal-motor segment stabilization.